2018
DOI: 10.1016/j.physa.2018.03.013
|View full text |Cite
|
Sign up to set email alerts
|

Extractive multi-document summarization using multilayer networks

Abstract: Huge volumes of textual information has been produced every single day. In order to organize and understand such large datasets, in recent years, summarization techniques have become popular. These techniques aims at finding relevant, concise and non-redundant content from such a big data. While network methods have been adopted to model texts in some scenarios, a systematic evaluation of multilayer network models in the multi-document summarization task has been limited to a few studies. Here, we evaluate the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(29 citation statements)
references
References 41 publications
1
28
0
Order By: Relevance
“…It is further suggested that the syntactic parsing can enhance the performance of summarizers. Tohalino and Amancio (2018) discuss a multilayer approach based extractive summarizer where several measurements such as degree, strength, page rank, accessibility, symmetry, shortest path, absorption time, etc., are used to weight the edges in the network of documents. They find that the distinction between intra-and inter-layer edges can play a major role in improving the results of a summarizer.…”
Section: A Graph Based Methodsmentioning
confidence: 99%
“…It is further suggested that the syntactic parsing can enhance the performance of summarizers. Tohalino and Amancio (2018) discuss a multilayer approach based extractive summarizer where several measurements such as degree, strength, page rank, accessibility, symmetry, shortest path, absorption time, etc., are used to weight the edges in the network of documents. They find that the distinction between intra-and inter-layer edges can play a major role in improving the results of a summarizer.…”
Section: A Graph Based Methodsmentioning
confidence: 99%
“…Sentences in the same document are connected at the same layer, while sentences in different documents are connected at different layers. is method effectively improves the quality of summary generation [21]. Marinho et al analyzed the author's attribution of documents based on the motif structure in complex networks.…”
Section: Application Of Complex Network In Natural Languagementioning
confidence: 99%
“…Text graph representation has been used for keyword extraction [3,[11][12][13][14][15][16][17][18][19]], text summarization [32], and language classification [33]. Modeling text as graphs has also been used for PLOS ONE text semantic analysis including information retrieval [34,35] and authorship attribution analysis [36,37], and word sense disambiguation [38,39].…”
Section: Modeling Text As Graphsmentioning
confidence: 99%